The influence of e-service quality, trust, brand image on Shopee customer satisfaction and loyalty - Dola Fitritha Raras Handayani; Retno Widowati PA; Nuryakin Nuryakin (Jurnal Siasat Bisnis, 2021)
Purpose: This research's main objective is to determine the relationship among e-service quality, trust, and brand image to customer loyalty. Customer satisfaction was a mediator which focused on Shopee customers in Yogyakarta.Design/methodology/approach: The research respondents consisted of 245 customers. The reliability and validity tests were conducted. The collected data were analyzed using the SEM AMOS method.Findings: The research results showed that: 1) e-service quality had a positive and significant influence on customer loyalty; 2) trust had a positive and significant influence on customer loyalty; 3) brand image had a positive and significant influence on customer satisfaction; 4) e-service quality had a positive and significant influence on customer loyalty; 5) customer trust had a positive and significant influence on customer loyalty; 6) brand image had a positive and significant influence on customer loyalty; 7) customer satisfaction had a positive and significant influence on customer loyalty; 8) e-service quality had a direct influence on customer loyalty without customer satisfaction as a mediator; 9) trust had a direct influence on customer loyalty without customer satisfaction as a mediator; 10) brand image had a direct influence on customer loyalty without customer satisfaction as a mediator.Research limitation/implications:  The research sample was Shopee customers in the Special Region of Yogyakarta. There had not been an analysis of other factors that influence customer satisfaction and loyalty, such as social risk and time risk. Practical implications: Future research should expand the research sample to Shopee customers outside of Yogyakarta Special Region. For further research, it is recommended to modify the proposed model so that the goodness of fit criteria obtained will be fulfilled by the good criteria.Originality/value:  In the context of customer satisfaction and loyalty, this research had offered an empirical research model on the relationship among e-service quality, trust, brand image, customer satisfaction and customer loyalty on Shopee customers outside of Yogyakarta Special Region. The use of satisfaction had mediating influence of e-service quality, trust, brand image on customer loyalty.